COMMUNITY OF CHILDREN INMATES AND ASSISTANCE SYSTEM IN THE PENITENTIARY: The Impact of Child Social System to the Assistance Process at Kutoarjo Children Penitentiary - Utari, Indah Sri (INDONESIAN JOURNAL OF CRIMINAL LAW STUDIES, 2017)
The community of inmates children as a unique and unique social system is difficult to understand when viewed only from the outside, so it is necessary to systematically attempt to know the values, norms, relationships, and objectives-through where and with what they are living, and understand both their own experiences and the world in which they liveThe situational system of the inmates children as human beings (although in this case is the child) to be fostered, is one of the important elements in the whole process of assistance in the Penitentiary is no exception to the Children Penitentiary in Kutoarjo. The entire penitentiary system design, from the assistance program, the assistance mechanism, and the assistance implementation, is actually determined by the circumstances and the reality of the people who are to be fostered, the inmates.The reality of the children inmates who are always on the "social order" in their various communities is essentially constantly changing. Specifically, this study finds links between: the institutional reality of a children penitentiary, which includes the factual circumstances concerning facilities and infrastructure, and the administrative aspects of KutoarjoChildren Penitentiary. The reality of the member of KutoarjoChildren Penitentiaryin the form of identified number of occupants, placement systems, and formal and informal groupings of the targeted children in addition to the build and formed a community of the assisted children in KutoarjoChildren Penitentiary and the basic elements of the Social System of the Auxiliaries in all the community of assisted children and etc.As Soerjono Sukanto said that even though human "convicts" live in a confined state, they instinctively want to interact with fellow inmates. This instinct is referred to as "gregariousness" (Soekanto: 1998: 73), which in the last instance will give birth to so-called "social groups". In this context created social structure, social system, norms and so on.